GRAFTING TEMBAGA(II) PADA SILIKA MODIFIKASI - Syukri - (Universitas Andalas, 2011)
ABSTRACT A copper(II) acetonitrile complex has been grafted on modified silica and characterized by Fouruer Transform Infra Red (FTIR) and Energy Dispersive X-ray (EDX). The succesful experiment was confirmed by the appearance of shifted CN stretching vibration of acetonitrile on modified silica surface (FTIR analysis). The amount of copper(II) loaded by the silica was of 7 % proven by EDX measurement. Key words: Grafting process, modified silica, metal loading